From Whole Gene Deletion to Point Mutations of EP300‐Positive Rubinstein–Taybi Patients: New Insights into the Mutational Spectrum and Peculiar Clinical Hallmarks. Issue 2 (4th November 2015) - Negri, Gloria; Magini, Pamela; Milani, Donatella; Colapietro, Patrizia; Rusconi, Daniela; Scarano, Emanuela; Bonati, Maria Teresa; Priolo, Manuela; Crippa, Milena; Mazzanti, Laura; Wischmeijer, Anita; Tamburrino, Federica; et al.
Abstract : Rubinstein–Taybi syndrome (RSTS) is a rare neurodevelopmental disorder characterized by both clinical and genetic heterogeneity: actually about 50% of cases are due to CREBBP mutations and about 10% to EP300 alterations. In this work, we expanded the EP300 mutational spectrum in RSTS cases describing six novel de novo alterations, including the first whole gene deletion, and we highlight peculiar clinical findings of this patients' subset: maternal gestosis, dermatological features, back malformations and typical behaviour predisposing to anxiety. ABSTRACT: Rubinstein–Taybi syndrome (RSTS) is a rare congenital neurodevelopmental disorder characterized by growth deficiency, skeletal abnormalities, dysmorphic features, and intellectual disability. Causative mutations in CREBBP and EP300 genes have been identified in ∼55% and ∼8% of affected individuals. To date, only 28 EP300 alterations in 29 RSTS clinically described patients have been reported. EP300 analysis of 22 CREBBP ‐negative RSTS patients from our cohort led us to identify six novel mutations: a 376‐kb deletion depleting EP300 gene; an exons 17–19 deletion (c.(3141+1_3142‐1)_(3590+1_3591‐1)del/p.(Ile1047Serfs*30)); two stop mutations, (c.3829A>T/p.(Lys1277*) and c.4585C>T/p.(Arg1529*)); a splicing mutation (c.1878‐12A>G/p.(Ala627Glnfs*11)), and a duplication (c.4640dupA/p.(Asn1547Lysfs*3)). All EP300 ‐mutated individuals show a mild RSTS phenotype and peculiar findings including maternal gestosis, skin manifestation, especially nevi or keloids, back malformations, and a behavior predisposing to anxiety. Furthermore, the patient carrying the complete EP300 deletion does not show a markedly severe clinical picture, even if a more composite phenotype was noticed. By characterizing six novel EP300 ‐mutated patients, this study provides further insights into the EP300 ‐specific clinical presentation and expands the mutational repertoire including the first case of a whole gene deletion. These new data will enhance EP300‐ mutated cases identification highlighting distinctive features and will improve the clinical practice allowing a better genotype–phenotype correlation.